The Link between Remittance and Economic Growth: An ARDL Bound Testing Approach - Dhungel, Kamal Raj (NRB Economic Review, 2018)
From the couple of decades remittances have been playing an important role in the Nepalese economy. For people of rural areas even for the urban households, remittance is becoming the major source of livelihood. Therefore, this study considers remittance as a focus variable with an aim to assess the link between remittance and growth. Autoregressive distributed lag (ARDL) model is applied to examine the relationship between remittance and growth. All the variables included in the analysis became stationary after first difference. The result of bound test confirms that the variables are cointegrated. It means the variables have long run relationship. The empirical result reveals that one percent increase in remittance increases the GDP by 0.36 percent in the long run. Similarly, the gross fixed capital formation, secondary school enrolment and the trade openness and per capita GDP have positive relationship. It implies that one percent increase in capital, labor and trade openness increases the per capita GDP by 0.82 percent, 0.46 percent and 0.30 percent in the long run respectively.